The economic effects of private equity buyouts - Steven J. Davis; John C. Haltiwanger; Kyle Handley; Ben Lipsius; Joshua Lerner; Javier Miranda (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2021)
We examine thousands of U.S. private equity (PE) buyouts from 1980 to 2013, a period that saw huge swings in credit market tightness and GDP growth. Our results show striking, systematic differences in the real-side effects of PE buyouts, depending on buyout type and external conditions. Employment at target firms shrinks 13% over two years in buyouts of publicly listed firms but expands 13% in buyouts of privately held firms, both relative to contemporaneous outcomes at control firms. Labor productivity rises 8% at targets over two years post buyout (again, relative to controls), with large gains for both public-to-private and private-to-private buyouts. Target productivity gains are larger yet for deals executed amidst tight credit conditions. A post-buyout widening of credit spreads or slowdown in GDP growth lowers employment growth at targets and sharply curtails productivity gains in public-to-private and divisional buy-outs. Average earnings per worker fall by 1.7% at target firms after buyouts, largely erasing a pre-buyout wage premium relative to controls. Wage effects are also heterogeneous. In these and other respects, the economic effects of private equity vary greatly by buyout type and with external conditions.
Keywords: D22; D24; G24; G34; J63; L25; 330; Private equity buyouts; business cycle; business dynamics; real effects; job creation; productivity; wages; administrative data; large matched sample